The Arctic Scramble Revisited: The Greenland Consortium and the Imagined Future of Fisheries in 1905 - Priebe, Janina (Journal of Northern Studies, 2015)
Among the numerous phrases that depict imagined futures in the North, the belligerent rhetoric of an Arctic scramble stands out. The notion of seizing opportunities continues to surface in current debates on resource exploration in the Arctic. This article places the present scramble in Greenland in a longer historical context. It analyses the arguments of a stakeholder group that applied in 1905 to the Danish Home Office for private access to Greenland’s natural resources, and that hoped to introduce trade with the colony’s products on a for-profit basis. The arguments of this initiative offer an insight into how the urgency to act was constructed through the authority of science. This paper suggests that the scramble for the Arctic lent a common framework to otherwise inconsistent narratives. Although the consortium’s attempt to privatize Greenlandic fisheries and other resource industries was halted in 1906, their narratives highlighted perceived mismanagement by the colonial administration and anticipated and helped shape long-term changes in policy.